Current issues and trends in e-government research - Norris, Donald F. (Hershey, PA : Cybertech Pub., 2007)
"This book provides a complete synopsis of the latest technologies in information policy, security, privacy, and access, as well as the best practices in e-government applications and measurement, as well as the most current issues in hardware and software technology, adoption, diffusion, planning, management and philosophy"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Information technology -- Research; Electronic government information; Public administration -- Technological innovations